PENGARUH DAYA TARIK IKLAN POINT COFFEE DI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN - Fikry Ferdyansyah (2021)
Nowadays coffee is one of the drinks that are often consumed by the people of Indonesia. Drinking coffee has also emerged as one of the unrewithable needs in the lives of many people, especially coffee lovers. Coffee itself has developed not only as a necessity for coffee lovers but also as a lifestyle. The increasing demand for coffee provoked the emergence of various brands and coffee shops around the community. One of them is Point Coffee which participates in it. Because of the large number of competitors, it is inecessary to advertise in order to compete with others. Point Coffe uses instagram as a medium for advertising. It is expected that point coffee ads on Instagram can influence purchasing decisions. This research was conducted using quantitative approach. The research method used is survey. The population of this study is Instagram followers @PointCoffeeid with a sample number of 100 respondents. Data testing techniques using SPSS version 21 programs. The results of this study showed that the correlation of variable X with variable Y was 0.417. Based on ithe results of the calculation of coefesien determination obtained the result of the influence of variable X on variable Y by 17.4%. Thus it can be concluded H0 was rejected and Ha accepted.